Are There Global Syndemics?. Issue 1 (2nd January 2022) - Singer, Merrill; Bulled, Nicola; Leatherman, Thomas
ABSTRACT: In this article, we address the nature of syndemics and whether, as some have asserted, these epidemiological phenomena are global configurations. Our argument that syndemics are not global rests on recognition that they are composed of social/environment contexts, disease clusters, demographics, and biologies that vary across locations. These points are illustrated with the cases of syndemics involving COVID-19, diabetes mellitus, and HIV/AIDS. We draw on theoretical discourse from epidemiology, biology, and anthropology to present what we believe is a more accurate framework for thinking about syndemics with shared elements.